2011
DOI: 10.1142/s0217732311036401
|View full text |Cite
|
Sign up to set email alerts
|

Investigations in the Lee–wick Electrodynamics

Abstract: We consider the Lee–Wick (LW) electrodynamics, i.e. the U(1) gauge theory where a (gauge-invariant) dimension-6 operator containing higher derivatives is added to the free Lagrangian of the U(1) sector. A quantum bound on the LW heavy particle mass is then estimated by computing the anomalous electron–magnetic moment in the context of the aforementioned model. This limit is not only within the allowed range estimated by LW, it is also of the same order as that considered in early investigations on the possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 24 publications
2
41
0
Order By: Relevance
“…Therefore, we need not be afraid of the massive spin-1 ghost. It is worth mentioning that recently a quantum bound on the Lee-Wick heavy particle mass was found that is of the order of the mass of the Z 0 boson [38]. Actually, this is a very important result.…”
Section: ¼ 0 (Lee-wick Electrodynamics)mentioning
confidence: 90%
“…Therefore, we need not be afraid of the massive spin-1 ghost. It is worth mentioning that recently a quantum bound on the Lee-Wick heavy particle mass was found that is of the order of the mass of the Z 0 boson [38]. Actually, this is a very important result.…”
Section: ¼ 0 (Lee-wick Electrodynamics)mentioning
confidence: 90%
“…(20), which describes a particle of mass m = 1/ √ 2βc, widely discussed in [64]. Based on studies of the anomalous magnetic moment of the electron [66][67][68], the estimates that have been found were ( X i ) 0 ≤ 7. It is important to remember that, in our investigation, we have supposed the violation of the Lorentz symmetry to occur spontaneously, i.e., due only to the background tensors.…”
Section: Discussionmentioning
confidence: 99%
“…A recent estimative of the Lee-Wick mass is m LW ≃ 410 GeV/c 2 [18], which implies that ℓ < 3.4 × 10 −20 m. For some application of Lee-Wick model, see [19]. The variational principle leads us to the equation…”
Section: The Electromagnetism In the Presence Of A Minimal Lengthmentioning
confidence: 99%